Title IX at 50: Legitimating state domination of women's sport. (August 2022) - Hextrum, Kirsten; Sethi, Simran
At Title IX's 50th anniversary we address the contradictions embedded in liberal state reform. This anniversary provides a juncture to consider the limitations of seeking gender liberation through the state. While US law is often credited with revolutionizing athletic access for girls and women, we trace how the state stymied greater transformation efforts. Using poststructuralist and Black feminist state critiques, we show how Title IX utilized an assimilation approach to equity by inviting state domination into women's sports. This invitation expanded state power across four domains— definitional, protective, surveillance, and economic —which retained rather than disrupted heteropatriarchal, White, capitalist, dominance. We conclude with suggestions to reignite a movement for women's liberation that reimagines gender-equitable sports beyond the state's control for the forthcoming 50 years.